Ethnographic Contributions To The Study of The National Labor Problem: The Case of Southern Peru Copper Corporation - Bausch, Elizabeth A. (1988)
This paper addresses, in general, the methodological debate on the problem of labor, seeking to underline the importance of empirical research. The author uses ethnographic data on the workers and syndicates of the Southern Peru Cooper Corporation, so as to illustrate the importance of empirical studies in the discovery of social and historical data which increases our understanding of the complex relationships between capital and labor. Similarly, it attempts to correct the erroneous observations on the same workers presented in the work of the American scholar David Becker, where the danger of treating ethnographic research on too superficially is clearly noted.